Muting Israeli Democracy : How Media and Cultural Policy Undermine Free Expression - Schejter, Amit (Book collections on Project MUSE., 2009)
The result of years of critical analysis of Israeli media law, this book argues that the laws governing Israeli electronic media are structured to limit the boundaries of public discourse. Amit M. Schejter posits the theory of a "mute democracy," one in which the media are designed to provide a platform for some voices to be heard over others. While Israel's institutions may be democratic, and while the effect of these policies may be limited, this book contends that free speech in Israel is institutionally muted to ensure the continued domination of the Jewish majority and its preferred interpretation of what Israel means as a Jewish-democratic state. Analyzing a wide range of legal documents recorded in Israel from 1961 to 2007, Muting Israeli Democracy demonstrates in scrupulous detail how law and policy are used to promote the hegemonic national culture through the constraints and obligations set on electronic media. -- Description from http://www.booktopia.com.au (Oct. 7, 2011).